Dynamical transmission of Varicella Virus in Jordan with SVIR Model through analysis and numerical simulations (Journal of Mathematical Modeling and Fractional Calculus, 2025)
Chickenpox, another name for varicella virus, is a highly contagious illness. In this work, we use mathematical modelling and simulation to examine the dynamics of transmission and propose an SVIR model for the varicella virus in Jordan. The dynamics of the population in various classes are examined using a suggested model, which offers a more thorough comprehension of the course of the epidemic and the efficacy of control efforts. Lipschitz condition and fixed-point theory were also used to establish the solution's existence and uniqueness. Additionally, using figures and mathematics, it investigates the effects of different factors on the reproductive number and sensitivity analysis of the suggested model. The Routh-Hurwitz stability criterion is used to determine local stability at equilibrium sites that are both disease-free and endemic. Lyapunov functions with the first derivative test used to establish the global stability of model equilibria analysis for both >1 and
Keywords: Varicella virus; Routh-Hurwitz stability; Sensitivity analysis; Basic reproduction Number.